2020
DOI: 10.3389/fncel.2020.566418
|View full text |Cite
|
Sign up to set email alerts
|

K+ Channels in Primary Afferents and Their Role in Nerve Injury-Induced Pain

Abstract: Sensory abnormalities generated by nerve injury, peripheral neuropathy or disease are often expressed as neuropathic pain. This type of pain is frequently resistant to therapeutic intervention and may be intractable. Numerous studies have revealed the importance of enduring increases in primary afferent excitability and persistent spontaneous activity in the onset and maintenance of peripherally induced neuropathic pain. Some of this activity results from modulation, increased activity and /or expression of vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 386 publications
(725 reference statements)
0
47
0
1
Order By: Relevance
“…It is generally agreed that small and medium DRG neurons are likely to convey pain and temperature information. In contrast, large DRG neurons are more likely to transfer mechanoreceptive details [36,38]. In our recent study, KMUP-1 was observed to have a strong analgesic effect in thermal hyperalgesia and had a modest impact on mechanical allodynia, suggesting that it could be more sensitive on Aδ and C fibers than on Aβ fibers [27].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…It is generally agreed that small and medium DRG neurons are likely to convey pain and temperature information. In contrast, large DRG neurons are more likely to transfer mechanoreceptive details [36,38]. In our recent study, KMUP-1 was observed to have a strong analgesic effect in thermal hyperalgesia and had a modest impact on mechanical allodynia, suggesting that it could be more sensitive on Aδ and C fibers than on Aβ fibers [27].…”
Section: Discussionmentioning
confidence: 91%
“…SNL and SNI have also preferred animal protocols by which to simulate human neuropathic pain. Both CCI and SNL are favored to investigate the effect of nerve injury on K + channel function [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These sensitize sensory nerve endings, attract macrophages and lymphocytes, alter gene expression, promote post-translational modification of proteins and alter ion channel function (17)(18)(19)(20)(21)(22)(23). The activity and/or expression of voltage-gated TTX-sensitive Na + channels, voltage-gated Ca 2+ channels, ASIC channels, TRP channels, and HCN channels is increased (24)(25)(26)(27) whereas that of K + channels is decreased (28). These peripheral ion channels thus present a viable target for therapeutic intervention (24,28) as alterations in their activity underlies the increased excitability of primary afferents (11,12,(29)(30)(31)(32)(33)(34)(35).…”
Section: Introductionmentioning
confidence: 99%
“…The activity and/or expression of voltage-gated TTX-sensitive Na + channels, voltage-gated Ca 2+ channels, ASIC channels, TRP channels, and HCN channels is increased (24)(25)(26)(27) whereas that of K + channels is decreased (28). These peripheral ion channels thus present a viable target for therapeutic intervention (24,28) as alterations in their activity underlies the increased excitability of primary afferents (11,12,(29)(30)(31)(32)(33)(34)(35). In the interest of brevity, this review is confined to description of injury-induced changes in voltage-gated cation channels in primary afferent neurons and their potential as therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%